Chemistry and Pharmacology of the Kazakh Crataegus Almaatensis Pojark: An Asian Herbal Medicine - Sabrina S. Soares; Elmira Bekbolatova; Maria Dulce Cotrim; Zuriyadda Sakipova; Liliya Ibragimova; Wirginia Kukula-Koch; Thais B. Sardella Giorno; Patrícia D. Fernandes; Diogo André Fonseca; Fabio Boylan (MDPI AG, 2019)
Crataegus almaatensis, an endemic ornamental plant in Kazakhstan is used in popular medicine due to its cardiotonic properties. The most studied species of the same genus are commonly found in Europe, which shows the importance of having the Kazakh species validated via its chemical and pharmacological studies. High-speed countercurrent chromatography (HSCCC) operated under optimized conditions enabled an isolation of the three main compounds from the aqueous phase of the leaves ethanol extract, further identified by nuclear magnetic resonance (NMR), as quercetin 3-O-rhamnoside (quercitrin) (4.02% of the crude extract-CECa); quercetin 3-O-β-galactoside (hyperoside) (1.82% of CECa); kaempferol 3-O-α-L-rhamnoside (afzelin) (0.94% of CECa). The CECa, the aqueous phase of the crude extract (APCa) together with the isolates were evaluated for their vascular (vascular reactivity in human internal mammary artery-HIMA), anti-nociceptive (formalin-induced liking response and hot plate) and anti-inflammatory (subcutaneous air-pouch model-SAP) activities. CECa at the concentrations of 0.014 and 0.14 mg/mL significantly increased the maximum contractility response of HIMA to noradrenaline. The APCa CR curve (0.007−0.7 mg/mL) showed an intrinsic relaxation effect of the HIMA. APCa at the dose of 100 mg/kg i.p. significantly decreased the total leukocyte count and the IL-1β release in the SAP wash.